Analisis Perbandingan Kinerja Keuangan PT. ABC, Tbk. Sebelum dan Sesudah Mengakuisisi PT. DEF,Tbk - Marni Marni; Elisabet Pali; Stefani M. Palimbong (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This study aims to determine the financial performance before and after the acquisition listed on the Indonesian Stock Exchange. This type of research is quantitative comparative, this research is to compare financial performance before and after the acquisition. This study uses quantitative data types, meaning that in analyzing the data used is data in the form of numbers. The unit of observation in this study is the 2016-2020 financial statements of PT ABC, Tbk. Data analysis methods used in this research are profitability ratios, liquidity ratios, solvency ratios and activity ratios by comparing the financial performance before and after the acquisition. Based on the results of research showing that financial performance as measured by financial ratios ROA, ROE, NPM, CR, QR, TATO and FATO has decreased after the acquisition compared to before the acquisition. The DAR, DER, and ITO ratios have increased after the acquisition compared to before the acquisition. The acquisition strategy has not been fully achieved within 2 years due to the condition of the financial performance of PT ABC Tbk. before the acquisition is better than after the acquisition.